2022
DOI: 10.3389/fbioe.2022.831288
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of In Situ Grown Hydroxyapatite Nanoparticles Modified Porous Polyetheretherketone Matrix Composites to Promote Osteointegration and Enhance Bone Repair

Abstract: The repairment of critical-sized bone defects is a serious problem that stimulates the development of new biomaterials. In this study, nanohydroxyapatite (nHA)-doped porous polyetheretherketone (pPEEK) were successfully fabricated by the thermally induced phase separation method and hydrothermal treatment. Structural analysis was performed by X-ray diffraction. The water contact angles and scanning electron microscopy were measured to assess physical properties of surfaces. The mechanical strength of the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The contact angle was used to detect the hydrophilicity of the samples. A hydrophilic material surface can effectively promote cell infiltration and adhesion [ 33 ]. The contact angles of each group of materials indicate that all samples present hydrophilic property, indicating that all samples perform hydrophilic properties ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The contact angle was used to detect the hydrophilicity of the samples. A hydrophilic material surface can effectively promote cell infiltration and adhesion [ 33 ]. The contact angles of each group of materials indicate that all samples present hydrophilic property, indicating that all samples perform hydrophilic properties ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…70 In addition to the excellent mechanical properties, in vivo and in vitro experiments have shown that the composite is non-cytotoxic and has higher osteogenicity and cell adhesion than pure PEEK materials. 71 Sun et al 72 found that Ca 2+ released from HA could activate the adhesion proteins FAK upon entry into the cell by increasing the level of HA the intracellular Ca 2+ concentration was increased, thus promoting the expression of adhesion proteins/genes. For the fused filament fabrication (FFF) fabricated PEEK/HA scaffolds, HA particles are evenly distributed throughout the bulk and across the surface of the native 3D printed samples.…”
Section: Bioactive Materials Modified Peekmentioning
confidence: 99%
“…NPs used in biomedical applications generally have an average size of between 10 and 100 nm [92]. They can be produced from different types of materials, such as ceramics, natural and synthetic polymers, metals, and organic materials [93,94], and they are generally combined with different matrices to develop nanocomposite scaffolds [95,96].…”
Section: Nanotechnologymentioning
confidence: 99%